In Good Faith? An Analysis of the Features and Outcomes of Duty of Fair Representation Cases - McQuarrie, Fiona (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2010)
While the union’s duty of fair representation (DFR) toward its members is well established in Canadian labour law, relatively little research has examined Canadian DFR cases or factors that may affect the outcome of DFR complaints. This paper examines 138 DFR cases filed with the British Columbia Labour Relations Board between 2000 and 2006. Only eight of the 138 cases resulted in a decision in favour of the complainant. The most common reasons for DFR complaints were the union’s alleged failure to pursue grievances relating to termination or to pursue grievances relating to job changes. The majority of complainants represented themselves in the process. Future research could expand upon these findings to improve understanding of the duty of fair representation and its application.